Transcriptome analysis of H2O2-treated wheat seedlings reveals a H2O2-responsive fatty acid desaturase gene participating in powdery mildew resistance. - Aili Li; Rongzhi Zhang; Lei Pan; Lichuan Tang; Guangyao Zhao; Mingzhu Zhu; Jinfang Chu; Xiaohong Sun; Bo Wei; Xiangqi Zhang; Jizeng Jia; Long Mao (PLoS ONE)
Hydrogen peroxide (H(2)O(2)) plays important roles in plant biotic and abiotic stress responses. However, the effect of H(2)O(2) stress on the bread wheat transcriptome is still lacking. To investigate the cellular and metabolic responses triggered by H(2)O(2), we performed an mRNA tag analysis of wheat seedlings under 10 mM H(2)O(2) treatment for 6 hour in one powdery mildew (PM) resistant (PmA) and two susceptible (Cha and Han) lines. In total, 6,156, 6,875 and 3,276 transcripts were found to be differentially expressed in PmA, Han and Cha respectively. Among them, 260 genes exhibited consistent expression patterns in all three wheat lines and may represent a subset of basal H(2)O(2) responsive genes that were associated with cell defense, signal transduction, photosynthesis, carbohydrate metabolism, lipid metabolism, redox homeostasis, and transport. Among genes specific to PmA, 'transport' activity was significantly enriched in Gene Ontology analysis. MapMan classification showed that, while both up- and down- regulations were observed for auxin, abscisic acid, and brassinolides signaling genes, the jasmonic acid and ethylene signaling pathway genes were all up-regulated, suggesting H(2)O(2)-enhanced JA/Et functions in PmA. To further study whether any of these genes were involved in wheat PM response, 19 H(2)O(2)-responsive putative defense related genes were assayed in wheat seedlings infected with Blumeria graminis f. sp. tritici (Bgt). Eight of these genes were found to be co-regulated by H(2)O(2) and Bgt, among which a fatty acid desaturase gene TaFAD was then confirmed by virus induced gene silencing (VIGS) to be required for the PM resistance. Together, our data presents the first global picture of the wheat transcriptome under H(2)O(2) stress and uncovers potential links between H(2)O(2) and Bgt responses, hence providing important candidate genes for the PM resistance in wheat.